First bioarchaeological evidence of the familial practice of embalming of infant and adult relatives in Early Modern France - Caroline Partiot; Maryelle Bessou; Sacha Kacki; Maxime Penet; Géraldine Sachau-Carcel; Dominique Castex (Scientific Reports)
Abstract While medieval and modern embalming practices in Western Europe are attested to historically and bioarcheologically, especially for famous historical figures, there are few recorded occurrences of this type of corpse preparation for a large number of archaeological individuals from the same lineage. Moreover, evidence of such practices mainly concerns adult individuals, whereas traces of child embalming are extremely rare. In 2017, the discovery of a crypt in the chapel of the Château des Milandes (Castelnaud-la-Chapelle, Dordogne, France) revealed a collective burial of the scattered remains of seven adults and five children of the aristocratic Caumont family, who died in the 16th and 17th centuries and whose skeletons all show marks of embalming practices. In 2021, another excavation in the chapel uncovered the individual grave of an elderly woman whose body was also embalmed. This skeletal sample provides a unique opportunity to examine the modus operandi of medieval embalming through the cutmarks left on the cranium and appendicular skeleton and to compare mortuary protocols for adults and children. Our macroscopic and microscopic investigations revealed a thorough and highly standardized technical treatment that was similar for both adult and very young immature individuals and displays a skillset that was passed down over two centuries.